Landslide activation during deglaciation in a fjord-dominated landscape: observations from southern Alaska (1984–2022) - J. Walden; J. Walden; M. Jacquemart; M. Jacquemart; B. Higman; R. Hugonnet; R. Hugonnet; R. Hugonnet; A. Manconi; A. Manconi; D. Farinotti; D. Farinotti (Natural Hazards and Earth System Sciences)
A consequence of the current global glacier mass loss is the destabilization of valley walls as the support provided by the glacier evolves and eventually vanishes. In this work, we examined the evolution of eight large, active landslides in southern coastal Alaska, a region experiencing some of the fastest glacier mass loss worldwide. Additionally, many glaciers in this area are retreating out of glacially carved fjords, leaving landslides in contact with deep waterbodies that can substantially increase the reach of a catastrophic failure through displacement waves or hazard cascades. We used automatic and manual feature tracking of optical imagery to derive slope movement from the 1980s to the present and compared this with glacier terminus retreat and thinning, precipitation, and seismic energy, paying particular attention to landslides in contact with lake or ocean water. We found that the majority of landslides underwent a pulse of accelerated motion during the studied time period. In four cases, landslide movement coincided with the rapid retreat of a lake- or marine-terminating glacier past the instability. At these sites and during these accelerations, the glacier retreat rates were up to 7 times higher than average, while the landslides reached velocities that were up to 9 times higher than their long-term average. At two sites where the landslides are still in contact with the ice, above-average precipitation and increased glacier thinning were found to coincide with accelerated motion, though conclusive causal links could not be drawn and the effect of short-term precipitation could not be ruled out. In two other cases, the landslides showed little to no movement, indicating that slopes may have complex and varied responses to large environmental changes. Our results suggest that landslides adjacent to lakes or fjords may be especially susceptible to sudden activation, which we propose is due to the particularly rapid retreat rates of water-terminating glaciers as well as mechanical and hydrological changes resulting from the replacement of ice with water at the landslide toe in relatively short timescales. By showing that glacier mass loss is associated with increased landslide movement across various settings in Alaska, we suggest that glacier–landslide interactions in coastal settings deserve special attention and further substantiate the need for establishing broader and more systematic paraglacial hazard monitoring in a warming world.